Underactuated soft hip exosuit based on adaptive oscillators to assist human locomotion - Tricomi, Enrica; Lotti, Nicola; Missiroli, Francesco; Zhang, Xiaohui; Xiloyannis, Michele; Müller, Thomas; Crea, Simona; Papp-Schmitt, Emese; Krzywinski, Jens; Vitiello, Nicola; Masia, Lorenzo (IEEE Robotics and automation letters, 2021)
Reproducing the mechanisms of human locomotion is a hard challenge. Assistive wearable devices in this context need to be lightweight, portable, and to adapt to the wearer’s walking pattern. Aiming to combine the aforementioned features, we developed a soft wearable exosuit to assist hip flexion during walking. The main feature of the device is underactuation, i.e., a single actuator is used to assist bilateral hip flexion. A control strategy based on Adaptive Oscillators and gait phase estimation is implemented to deliver flexible assistance and to adapt to changes in walking pattern. The system was tested on six healthy subjects. Preliminary results show good performance of the control algorithm to track human gait and to deliver symmetrical assistance to both legs. First kinematic and muscular assessments revealed promising results at walking speeds near to the natural human walking, where the device did not alter hip kinematics and decreased the effort required by muscles contributing to hip flexion. Once validated on a larger sample of subjects, the device can have the potentialities to be used in clinical and wellness applications.